2022
DOI: 10.3349/ymj.2022.63.3.252
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of miR-21-5p in Predicting Occurrence and Progression of Uremic Vascular Calcification in Patients with End-Stage Renal Disease

Abstract: Purpose Vascular calcification (VC) is a common complication of end-stage renal disease (ESRD). This study aimed to examine changes in the expression of miR-21-5p in ESRD patients with VC and to explore its clinical value in predicting the occurrence and progression of uremic VC. Materials and Methods 120 ESRD patients were divided into patients without VC group (n=38) and patients with VC group (n=82). All patients were followed up for 2 years to evaluate VC progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…miR-21 está elevado en modelos de podocitos lesionados y en casos de enfermedad renal crónica en proporción inversa a la tasa de filtración glomerular estimada, lo cual alienta a proponerlo como marcador pronóstico (31). En pacientes con enfermedad renal terminal, miR-21 ha mostrado ser un factor predictivo independiente de calcificación vascular, la cual juega un papel importante en la mortalidad de pacientes con esta condición (32).…”
Section: Enfermedades Pulmonaresunclassified
“…miR-21 está elevado en modelos de podocitos lesionados y en casos de enfermedad renal crónica en proporción inversa a la tasa de filtración glomerular estimada, lo cual alienta a proponerlo como marcador pronóstico (31). En pacientes con enfermedad renal terminal, miR-21 ha mostrado ser un factor predictivo independiente de calcificación vascular, la cual juega un papel importante en la mortalidad de pacientes con esta condición (32).…”
Section: Enfermedades Pulmonaresunclassified
“…Similarly, serum miR‐21‐5p levels were significantly higher in ESRD patients with VC in comparison to those without, and increased progressively as the severity of the condition worsened. Multivariable Cox regression analysis suggested that serum miR‐21‐5p is an independent predictive factor of VC progression in ESRD patients (Wu et al, 2022). Taken together, serum miRNAs can serve as a promising biomarker to predict the presence and, more importantly, progression of uremia‐associated VC.…”
Section: Introductionmentioning
confidence: 99%